Phylogeny based generic reclassification of Muscari sensu lato (Asparagaceae) using plastid and genomic DNA. Issue 2 (18th January 2023) - Böhnert, Tim; Neumann, Michael; Quandt, Dietmar; Weigend, Maximilian
Abstract: The grape hyacinth ( Muscari ) represents an important ornamental plant group in Asparagaceae subfamily Scilloideae, comprising some 80 species distributed mainly in the Mediterranean. However, genus delimitation has repeatedly shifted over the past two centuries and a general consensus has not been reached so far. The present study investigates the phylogeny of Muscari s.l. (i.e., including the disputed segregates Pseudomuscari and Leopoldia ) with a broad sampling of about half the currently recognized species using both chloroplast markers ( trnK ( matK )‐ psbA, trnL‐trnF, rpl16 ) and genome‐wide single nucleotide polymorphism (SNP) data generated by double‐digest restriction site‐associated DNA sequencing (ddRAD). We perform concatenated maximum likelihood inference for both datasets as well as a coalescent‐based approach and principal component analysis (PCA) on the ddRAD data. We find that the morphological characters traditionally used to distinguish different genera are not diagnostic for the clades here retrieved. Also, the segregates Pseudomuscari and Leopoldia are deeply nested in Muscari and we therefore propose a broadly defined Muscari with five subgenera. The subgenera roughly correspond to previously recognized entities, with the exception of the newly identified clade here proposed as M.  subg. Pulchella subg. nov. We provide a provisional assignment of the 80 currently accepted taxa to these subgenera.